Media Framing Analysis and Islamic Minority Sect - Dwi Putri Robiatul Adawiyah; Fifi Listia Sari; Agoes Moh. Moefad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
The process of forming the construction in the media is called framing. Shia framing in the Indonesian mass media is constructed in such a way because it is a minority group that is considered deviant. In this study, the author will explain how the online media BBC News Indonesia and Radar Bangsa frame the Islamic minority sect to their readers and the alignments of the two media in constructing the reality of the Islamic minority sect. This study uses a descriptive qualitative method using the analytical framework of Zhongdang and Kosicki by looking at the syntactic structure, script structure, thematic structure, and rhetorical structure. The results showed that BBC News and Radar Bangsa have different framing in presenting and presenting a fact. The difference in locality makes BBC News Indonesia have a wider perspective in delivering news about minority sects, but Radar Bangsa only discusses the small scope of the report.